A microchannel device for root hair isolation and behavior analysis. (11th October 2021) - Horade, M; Nishimura, S; Yamawaki, T; Yashima, M
Abstract: Despite the active development of microchannel devices for cell manipulation, there are few reports on such devices for plants than those for animal cells, including human cells. This paper presents root-hair isolation and observation methods for Arabidopsis thaliana roots by using a microchannel device. Specifically, to facilitate observation, the height and width of the channel were optimized so that only one A. thaliana root hair could pass through. As A. thaliana is a model organism for plant research, in this study, it was used in a experiment with the expectation that its application will expand in the future. In typical in vitro experimental systems, a gel-like medium is used; however, as this is difficult to introduce into the micron-order narrow space of a microchannel device, a liquid medium was used in this study. We established a protocol unique to microchannel devices and succeeded in isolating root hairs at channel heights and widths of at least 10 μ m and 10–14 μ m, respectively. Root-hair elongation was confirmed in the microchannel, and the deceleration of root-hair elongation rate was confirmed quantitatively. In a future work, based on the findings of this study, we intend to analyze the behavior of individual root hairs and clarify the correlation with repellent substances by exploiting the characteristics of microchannel devices. This research can potentially serve as a basis for future applied research of agricultural chemicals.